Student Support and Transition Through a Buddy Programme to Foster Social Integration (Journal of Student Affairs in Africa, 2021)
The University of Pretoria (UP) began offering formal academic student support in 2011 when the first faculty student advisor (FSA) was appointed. Although many more FSAs were subsequently appointed, assistance to all the students in need of support remained insufficient. However, financial assistance through the collaboration grant received from the Department of Higher Education and Training in 2018 made it possible to explore new areas of support. The UP was able to pilot four innovations due to the availability of additional funds. These included generic workshops across faculties; the creation of a hub in the library, which served as a common contact point for students requiring assistance; the appointment of peer advisors; and a Buddy Programme for first-year students. This article explains the Buddy Programme as perceived by the senior students who mentored the first-year students. The mentors are known as “big buddies”. Our work on this programme is based on Tinto’s (1975) ideas about social integration. The Buddy Programme was introduced to assist first-year students in their transition from school to university life. This paper highlights the challenges that first-year students faced and it explains how the concepts could become institutionalised once university activities have been normalised in the post-pandemic future.
Keywords: advising; mentoring; buddy system; peer support